Mild hypohydration decreases cycling performance in the heat - Bardis, C. N.; Kavouras, S. A.; Kosti, L.; Markousi, M.; Sidossis, L. S. (Medicine & Science in Sports & Exercise, 2013)
Introduction: Hypohydration exceeding 2% of body mass decreases exercise performance. However, the effects of mild hypohydration (<2%) are not clear. Purpose: The aim of this study was to determine the effects of mild hypohydration on cycling performance during a simulated-hill circuit course in a warm environment (32.5°C ± 0.5°C). Methods: Ten trained male cyclists (age, 30 ± 7 yr; mass, 78.4 ± 9.5 kg; height, 1.80 ± 0.01 m; V·O2max, 52.4 ± 3.3 mL/min·kg; and Powermax, 355 ± 29 W) performed a cycling circuit three times on a laboratory ergometer consisting of 5 km at 50% of maximum power output and 5 km at an all-out pace, followed by a 5-min rest every 5 km. Subjects started the performance test either euhydrated (EUH) or hypohydrated (HYP), by 0% ± 0% and -1.0% ± 0.1% of body mass, respectively. Results: Mean speed at the first, second, and third 5-km simulated-hill cycling was higher in the EUH (28.1 ± 3.1, 27.7 ± 3, and 27.0 ± 3.6 km/h) than that in the HYP trial (27.0 ± 2.9, 26.1 ± 3.7, and 25.9 ± 3.6 km/h) (P < 0.05). Mean power output at the first, second, and third 5-km simulated-hill cycling was greater in the EUH (284 ± 55, 266 ± 53, and 254 ± 58 W) than that in the HYP trial (272 ± 56, 250 ± 61, and 240 ± 57 W) (P < 0.05). Gastrointestinal temperature at the end of the first, second, and third 5-km simulated-hill cycling was greater in the HYP (38.3°C ± 0.4°C, 38.4°C ± 0.2°C, and 38.6°C ± 0.2°C) than that in the EUH trial (38.1°C ± 0.3°C, 38.1°C ± 0.3, and 38.3°C ± 0.3°C) (P < 0.05). Overall, sweat sensitivity during the circuit course was greater in the EUH (115 ± 58 g·/°C.min) versus HYP trial (67 ± 19 g/°C.min) (P < 0.05). Furthermore, RPE and heart rate were similar and near maximal between trials (P > 0.05). Conclusion: The data showed that mild hypohydration decreased cycling performance, possible by inducing greater thermal and cardiovascular strain.